2018
DOI: 10.5004/dwt.2018.22972
|View full text |Cite
|
Sign up to set email alerts
|

Heat carrier nanofluids in solar still – A review

Abstract: a b s t r a c tThis review discusses heat transfer enhancement of various nanoparticles in solar stills. The thermal conductivities of various nanoparticles, that is, SiC, and multiwalled carbon nanotubes suspended in water with different volume fractions are analyzed. The factors involved in the thermal conductivity and distillation enhancement of nanofluids are discussed. This review is crucial because thermal conductivity enhancement augments the fresh water yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 79 publications
0
13
0
1
Order By: Relevance
“…The research concluded that at lower salt concentrations of TDS of the seawater, SiC nanofluids showed excellent stability and higher thermal conductivity, which confirms the feasibility of the nanofluid for solar desalination. Kumar et al [31] reviewed the performance of heat carrier nanofluids for solar still applications and concluded that the output of solar still initially increases with the particle concentration in the nanofluid, but it deteriorates at higher particle concentrations due to the higher viscosity and increase in pressure drop in the system. A brief review of various nanofluids application in solar stills is outlined in table 5.…”
Section: Application Of Nanofluids For Thermal Desalinationmentioning
confidence: 99%
“…The research concluded that at lower salt concentrations of TDS of the seawater, SiC nanofluids showed excellent stability and higher thermal conductivity, which confirms the feasibility of the nanofluid for solar desalination. Kumar et al [31] reviewed the performance of heat carrier nanofluids for solar still applications and concluded that the output of solar still initially increases with the particle concentration in the nanofluid, but it deteriorates at higher particle concentrations due to the higher viscosity and increase in pressure drop in the system. A brief review of various nanofluids application in solar stills is outlined in table 5.…”
Section: Application Of Nanofluids For Thermal Desalinationmentioning
confidence: 99%
“…Because of the slow distillation process, various types of solar stills have been developed: solar stills with the dye in the basin, concentrator assisted solar still, tubular solar stills, spherical solar stills, etc. [52]. Arunkumar et al [52] reviewed the nanofluid based solar stills in terms of system productivity and enhancement.…”
Section: Solar Stillsmentioning
confidence: 99%
“…[52]. Arunkumar et al [52] reviewed the nanofluid based solar stills in terms of system productivity and enhancement. They concluded that using nanofluid increases the productivity (produced pure water mass per area, kg/m 2 ) as well as system thermal efficiency.…”
Section: Solar Stillsmentioning
confidence: 99%
“…The research concluded that at lower salt concentrations of TDS of the seawater, SiC nanofluids showed excellent stability and higher thermal conductivity, which confirms the feasibility of the nanofluid for solar desalination. Kumar et al [27] reviewed the performance of heat carrier nanofluids for solar still applications and concluded that the output of solar still initially increases with the particle concentration in the nanofluid, but it Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 4 December 2019 doi:10.20944/preprints201912.0048.v1…”
Section: Application Of Nanofluids For Thermal Desalinationmentioning
confidence: 99%